Thiomicrorhabdus sediminis sp. nov. and Thiomicrorhabdus xiamenensis sp. nov., novel sulfur-oxidizing bacteria isolated from coastal sediments and an emended description of the genus Thiomicrorhabdus. Issue 2 (27th February 2021) - Liu, Xuewen; Chen, Baoping; Lai, Qiliang; Shao, Zongze; Jiang, Lijing
Abstract : Two novel Gram-strain-negative and rod-shaped bacteria, designated strain G1 T and G2 T, were isolated from sediment samples collected from the coast of Xiamen, PR China. The cells were motile by a single polar flagellum. Growth of strain G1 T occurred at 10–40 °C (optimum, 30 °C), at pH 6.0–9.0 (optimum, pH 7.5) and with 5–1530 mM NaCl (optimum, 510 mM), while the temperature, pH and NaCl concentration ranges for G2 T were 4–45 °C (optimum, 28 °C), pH 5.5–8.0 (optimum, pH 6.5) and 85–1530 mM NaCl (optimum, 340 mM). The two isolates were obligate chemolithoautotrophs capable of using thiosulfate, sulfide, elemental sulphur or tetrathionate as an energy source. Strain G1 T used molecular oxygen or nitrite as an electron acceptor, while strain G2 T used molecular oxygen as the sole electron acceptor. The dominant fatty acids of G1 T and G2 T were summed feature 3 (C16:1 ω7 c and/or C16:1 ω6 c ), C16 : 0 and summed feature 8 (C18:1 ω7 c and/or C18:1 ω6 c ). The DNA G+C content of G1 T and G2 T were 45.1 and 48.3 mol%, respectively. Phylogenetic analysis based on 16S rRNA gene sequences indicated that strain G1 T and G2 T were members of the genus Thiomicrorhabdus, and most closely related to Thiomicrorhabdus hydrogeniphila MAS2 T (96.0 %) and Thiomicrorhabdus indica 13-15A T (95.4 %), respectively. The 16S rRNA gene sequence similarity between strains G1 T and G2 T was 95.8 %. Based on the phylogenetic, genomic and phenotypic data presented here, the isolate strains represent novel species of the genus Thiomicrorhabdus, for which the names Thiomicrorhabdus sediminis sp. nov. (type strain G1 T =MCCC 1A14511 T =KCTC 15841 T ) and Thiomicrorhabdus xiamenensis sp. nov. (type strain G2 T =MCCC 1A14512 T =KCTC 15842 T ) are proposed.